Design and Development of a Multi-Sided Tabletop Augmented Reality 3D Display Coupled with Remote 3D Imaging Module - Muhammad Saad; Shahid Iqbal; Shoaib R. Soomro (Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
This paper proposes a tabletop augmented reality (AR) 3D display paired with a remote 3D image capture setup that can provide three-dimensional AR visualization of remote objects or persons in real-time. The front-side view is presented in stereo-3D format, while the left-side and right-side views are visualized in 2D format. Transparent glass surfaces are used to demonstrate the volumetric 3D augmentation of the captured object. The developed AR display prototype mainly consists of four 40 × 30 cm2 LCD panels, 54% partially reflective glass, an in-house developed housing assembly, and a processing unit. The capture setup consists of four 720p cameras to capture the front-side stereo view and both the left- and right-side views. The real-time remote operation is demonstrated by connecting the display and imaging units through the Internet. Various system characteristics, such as range of viewing angle, stereo crosstalk, polarization perseverance, frame rate, and amount of reflected and transmitted light through partially reflective glass, were examined. The demonstrated system provided 35% optical transparency and less than 4% stereo crosstalk within a viewing angle of ±20 degrees. An average frame rate of 7.5 frames per second was achieved when the resolution per view was 240 × 240 pixels.